2003
DOI: 10.1002/jmv.10507
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of antibodies against 70 kDa heat shock proteins in the sera of patients with HIV infection

Abstract: Heat shock proteins (Hsp), especially 70 kDa heat shock protein (Hsp70) play an important role in the life cycle of HIV-1 virus. Hsp70 is overexpressed in HIV-infected cells and this is the most abundant Hsp associated with HIV virions. The aim of our study was to investigate whether HIV infection increases the extent of specific humoral immune response against Hsp70. The serum concentration of anti-Hsp70 IgG antibodies was measured in 47 HIV-infected patients, and 62 healthy, HIV-seronegative persons. Ninetee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Prohaszka et al (1999) reported that there was an increase of anti-hHsp60 and mycobacterial Hsp65 and a strong positive correlation between the levels of autoantibodies against C1q and antibodies to these Hsps in the sera of HIV-infected patients. There have been reports of an increase in serum Hsp70 and antibodies to Hsp70 in HIV-infected patients (Kocsis et al 2003). Antibodies to the Hsp70 cochaperone HspB1 have also been found in HIV-infected subjects but also in uninfected controls consistent with the absence of any relationship between the autoantibodies and clinical parameters (Papp et al 2005).…”
Section: Anti-hsps and Infectious Diseasesmentioning
confidence: 89%
“…Prohaszka et al (1999) reported that there was an increase of anti-hHsp60 and mycobacterial Hsp65 and a strong positive correlation between the levels of autoantibodies against C1q and antibodies to these Hsps in the sera of HIV-infected patients. There have been reports of an increase in serum Hsp70 and antibodies to Hsp70 in HIV-infected patients (Kocsis et al 2003). Antibodies to the Hsp70 cochaperone HspB1 have also been found in HIV-infected subjects but also in uninfected controls consistent with the absence of any relationship between the autoantibodies and clinical parameters (Papp et al 2005).…”
Section: Anti-hsps and Infectious Diseasesmentioning
confidence: 89%
“…Several studies reported increased expression of Hsp70 in HIV-1 infection and showed its presence in the virion (23,24,45). Therefore, we assessed the Hsp40 expression level in HIV-1-infected CEM-GFP cells by immunoblotting for Hsp40.…”
Section: Nl4-3 Nef Also Interacts With Hsp40 Both In Vitro and In Vivo-mentioning
confidence: 99%
“…Since our group was active in the study of the connection between antibodies against different heat shock proteins and coronary artery disease (Burian et al 2001;Kocsis et al 2003;Lu et al 2010;Prohaszka et al 1999;Veres et al 2002), we carried out B cell epitope analysis with sera of coronary artery disease. As to our best knowledge, only T cell epitopes of HSP60 have been analyzed until now in IBD (Puga Yung et al 2009).…”
Section: Introductionmentioning
confidence: 99%